FACTORS THAT AFFECT THE LEARNING OUTCOMES OF DRAWING WITH SOFTWARE (MDPL) COURSE OF STUDENTS OF GRADE XI TGB SMK N 1 KOTO XI TARUSAN - 1654-1673 , Asep Kuswadi (Universitas Negeri Padang, 2016)
ABSTRACT This research was motivated by the low of student’s learning outcomes in Drawing with Software (MDPL) course. The purpose of this research is to reveal factors that affect learning outcomes of Drawing with Sofware (MDPL) course of students of grade XI TGB SMK N 1 Koto XI Tarusan. The type of this research is descriptive quantitative and the population in this study is 25 students. Sample was taken by using total sampling, where all members of the population was used as sample. Data were collected using a questionnaire with likert scale consisting of five possible answers. The number of items in the questionnaire is 64 statement. The results showed that: (1) Internal factors, i.e. factors that comes from within the students, affect the learning outcomes with a percentage of 59,09 while the external factors, i.e. factors that come from outside the student, affect the learning outcomes with a percentage of 40.91%; (2) Among the aspects of internal factors that affect student’s learning outcomes, the most dominant influence is the physical factor with a percentage of 20.77% .Keywords: Learning Outcomes, Drawing with Software